The pathway of sodium from amniotic fluid to fetal blood - Bor, Naci M.; Juvelier, Bernard W.; Navarro, Antonio; Sciarra, Dorothea L.; Corbit, John D. (The Turkish Journal of Pediatrics, 1964)
In these experiments with pregnant sheep, the fetus was removed from the uterine cavity and with the umbilical circulation and the relationship of the fetal membranes to the decidua maintained, sodium fluorescein was added to the amniotic fluid. The possible contribution of the fetal lungs, gastrointestinal tract and the skin was therefore completely eliminated. The tracer was then identified in the fetal and maternal blood streams and its pathway from the amniotic cavity was traced step by step in each intervening organ. It is, therefore, concluded that the removal of sodium fluorescein from the amniotic cavity is affected by the fetal membranes lining the wall of the amniotic cavity and covering the umbilical cord. It is possible that other constituents of the amniotic fluid might also use this same route in their circulation.